Formal ethics - Gensler, Harry J. (Routledge, 1996)
Formal Ethics is the study of formal ethical principles. The most important of these, perhaps even the most important principle of life, is the golden rule: "Treat others as you want to be treated". Although the golden rule enjoys support amongst different cultures and religions in the world, philosophers tend to neglect it. Formal Ethics gives the rule the attention it deserves. Modelled on formal logic, Formal Ethics was inspired by the ethical theories of Kant and Hare. It shows that the basic formal principles of ethics, like the golden rule, are very similar to principles of logic, and gives a firm basis for our ethical thinking. As an introduction to moral rationality, Formal Ethics also considers non-formal elements, and is applied to areas of practical concern such as racism and moral education